Treaty tantrums: Past, present and future of a business and human rights treaty. Issue 3 (September 2022) - Deva, Surya
This column analyses the current process in the UN Human Rights Council to negotiate an international legally binding instrument to regulate, in international human rights law, the activities of transnational corporations and other business enterprises. It does so in the context of two previous attempts at the UN level to adopt binding rules for (multinational) corporations and the continued inability of international soft standards as well as hard rules at the national level in States in ensuring that businesses take their human rights responsibilities seriously. It is argued that an international treaty is desirable as part of a regulatory ecosystem to promote respect of human rights by business enterprises and to strengthen corporate accountability for human rights abuses. While the treaty should build on and complement the existing international soft standards, it should also try to fill some of the regulatory gaps that these standards might not ever be able to fill.